Effects of the conditions of the microemulsion preparation on the properties of Fe3O4 nanoparticles - Ha, Nguyen Thai; Hai, Nguyen Hoang; Luong, Nguyen Hoang; Chau, Nguyen; Chinh, Huynh Dang (VNU Journal of Science: Natural Sciences and Technology; Vol 24 No 1, 2008)
Abstract